2021
DOI: 10.3390/genes12091305
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Metabolism Regulators Associated with Cancer Development and the Tumor Microenvironment: A Pan-Cancer Multi-Omics Analysis

Abstract: Background: In recent years, metabolic reprogramming has been identified as a hallmark of cancer. Accumulating evidence suggests that glutamine metabolism plays a crucial role in oncogenesis and the tumor microenvironment. In this study, we aimed to perform a systematic and comprehensive analysis of six key metabolic node genes involved in the dynamic regulation of glutamine metabolism (referred to as GLNM regulators) across 33 types of cancer. Methods: We analyzed the gene expression, epigenetic regulation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…The enhanced glutamine in cancer cells activates mTOR signal transduction, inhibits endoplasmic reticulum stress, and promotes protein synthesis, thereby promoting tumor growth and proliferation (88)(89)(90). Moreover, our previous research revealed that glutamine metabolism regulators were associated with poorer cancer prognoses and an immunosuppressive TME (91). In the TME under hypoxic conditions, Glucose metabolism is the most common metabolic reprogramming of tumors that plays a major role in cancer survival, proliferation, metastasis, and treatment resistance (92)(93)(94)(95)(96).…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced glutamine in cancer cells activates mTOR signal transduction, inhibits endoplasmic reticulum stress, and promotes protein synthesis, thereby promoting tumor growth and proliferation (88)(89)(90). Moreover, our previous research revealed that glutamine metabolism regulators were associated with poorer cancer prognoses and an immunosuppressive TME (91). In the TME under hypoxic conditions, Glucose metabolism is the most common metabolic reprogramming of tumors that plays a major role in cancer survival, proliferation, metastasis, and treatment resistance (92)(93)(94)(95)(96).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have suggested that GLS2 expression is associated with good prognosis; for example, high expression of GLS2 in HCC is associated with a long survival time of patients 37 . However, most studies have shown that overexpression or amplification of GLS2 was associated with poor survival prognosis, such as in breast cancer 38,39 , glioblastoma 40 , ovarian cancer 41 , and lung cancer 34,42 . In addition, GLS2 was more highly expressed and regulated by METTL3 by m6A modification, which was significantly associated with poor prognosis in esophageal squamous cell carcinoma 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme kidneytype glutaminase (GLS or GLS1) participates in the catabolism of glutamine into glutamate in the mitochondria. This process is particularly crucial for highly proliferative cancer cells, as they often overexpress GLS to meet elevated energy and raw material requirements [19]. GLS is crucial for providing energy through α-ketoglutarate in the tricarboxylic acid (TCA) cycle [18].…”
Section: Discussionmentioning
confidence: 99%